The innovative design of automatic speed limiter device for trucks and buses based on road location analysis - Hadi Pranoto; Abdul Mutalib Leman; Dafit Feriyanto; Andi Adriansyah; Abdi Wahab (SINERGI, 2022)
The increasing number of vehicles every year has led to the rising potential of vehicle accidents. In 2015, there were 556 fatalities from 6,231 accident cases occurred in Jakarta, through regulation of the Minister of Transportation Republic Indonesia No: 111 in 2015, it has been issued firm vehicle speed restrictions, but there is no positive impact because the speed limit of each vehicle cannot be done automatically by the highway location, so the need for innovation to design a tool that can meet these needs. The method in this research is developing a device that can break the flow of fuel quickly to hold the vehicle's speed with a Global Positioning System (GPS) as a trigger to drive the relay that has been installed on the engine. The results of this study are devices that have been installed in truck and bus engines capable of holding the speed. The result shows that the voltage has been calculated was at 10 km/h produce 1.2 volts, and the highest speed of 70km/h produce 10.7 Volt. GPS in speed limiter is also compared with the Map application. The result shows a slight difference either in latitude or longitude, where the smallest differences in latitude and longitude were about 0.00" and 0.05", respectively. In addition, the GPS speed limiter well performs to limit the speed of trucks and buses for 32 km/h in pedestrians, 58km/h on the highway and 52 km/h on a toll road.